A organização e o desenvolvimento de estágios curriculares em cursos de licenciatura da UFSM: envolvimentos de estagiários e orientadores - Agostini, Sandra (2008)
This study aimed at collaborating to a better comprehension of Curricular Trainings organization and development in teachers formation courses. In this way, we are supposed to answer the following research question: How are the Curricular Trainings organization and development in teachers formation courses at UFSM characterized? . Our research worked with 13 courses: Languages-Portuguese; Languages-English; Languages-Spanish; Physical Education; Chemistry; Physics; Biology; Music; Mathematics; Philosophy; Geography; Visual Arts and History. As a source of information for our study, we have basically used the said courses Politic Pedagogical Projects (PPP) as well as the laws to Basic Education Teachers Formation in Brazil. Moreover, we did open questionnaires and group discussions to collect information with the trainee students besides collecting data with their Curricular Training advisors through structured interviews. The analysis showed that all the investigated courses adapted to 400 hours to the Curricular Training development. However, there is no pattern to the activities organization and development. From the trainee students narratives it was possible to perceive that generally most of them have had a good relation with their advisors since they were well received and also have had a good relation at schools. The subjects that most contributed to their Curricular Training development were the ones related to conceptual structure of the area. Most of the students (58,44%) have had orientation to get places at schools, most of the respondents considered their initial formation as an important moment of learning that permitted them to live their professional choice, however, some of them considered it as a negative experience phase due to the lack of discipline of students at schools that guided them to a disappointment in being teachers and they claimed not being prepared to that situation. In contrast, it was also possible to notice that schools do not follow the trainee students as well the responsible teachers almost do not contribute to the Curricular Training development. We could notice that this responsibility is centered at the High Education Institution (IES). All the advisors interviewed (12) used the subject that deal with didactic knowledge of the content to organize and guide the orientation meetings with the students. Most of them (83%) demonstrated to know about an agreement signed between UFSM and Public Educational Systems (Inter-Institutional Education Practices Program), however, it seems not having a specific function, neither practical or operational, since the respondents affirmed the necessity of signing a new agreement for the students to have support to access the schools. According to the advisors, there are many differences in Curricular Trainings development among schools, depending on the higher or lower tradition of schools in receiving trainees, on the exigency or not of following standard programs as High Education Ingress Program (PEIES) and on the higher or lower exigency that the school teachers work together with the trainees in their responsibilities. Throughout our study, we realized that for improving the initial formation, it is not enough the High Education Institution (IES) that must to ccomplish primary aspects of legal normative (such as the 400 hours of Curricular Training). It is necessary to search for ways of interaction that stimulate a intensive commitment among Basic Education Schools (EEB) and High Education Institution (IES), to provide attendance and help aiming at supporting trainee students difficulties like: lack of individual attendance, help and support throughout their trainings.